BIODIESEL PRODUCTION FROM SUDANESE JATROPHA CURCAS SEED BY THE ALKALI-CATALYZED TRANSESTERIFICATION PROCESS AND ITS ANALYSIS BY GAS CHROMATOGRAPHY - Mahmoud Ahmed Abdalla, Arij
Sudan is highly dependent on diesel. Diesel is used in agriculture machines, transportation, and other applications. This study has been carried out to manufacture biodiesel from Jatropha curcas seed oil. Jatropha was chosen because it is not edible there will not pose a new problem to humans regarding food competition. This research successfully extracted oil from Jatropha curcas seed using n-hexane solvent with a 39% yield. Jatropha curcas seed oil was then analyzed and compared to a standard specification. The oil than converted to biodiesel by alkaline transesterification process with a conversion yield of 92 %. The properties such as flash point, acid value, viscosity, iodine value, density, copper corrosion, cetane number, sulphated ash, pour point, free glycerol, and total glycerol contents were 174?, 0.17mg KOH/g, 8.912 mm2/s, 102 g I2/100 g, 895.8 kg/m3, class1.51, 0.0047 %, -3 ?, 0.01 %,0.03 %, respectively. These quantities obtained were compared with ASTM D6751, EN14214, and ASTM 975 specifications. Those properties showed the biodiesel produced met most of the biodiesel standards. The GC-MS data showed the FAME has a 16-22 carbon chain and still has monoglycerides, diglycerides, and triglycerides.